Konsep Perkembangan Peserta Didik Perspektif Al-Qur’an dan Hadis - Feni Mardika; Wahidah Fitriani (Indonesian Journal of Islamic Education Studies (INJURIES), 2023)
The concept of student development from an Al-Qur'an and Hadith perspective will be discussed in this research. This research aims to explain the concept of development in the Al-Qur'an, the tasks of student development in the Al-Qur'an and hadith guidelines and the factors that influence students' development in the Al-Qur'an and hadith. This research was carried out using the library research method, by reading, reviewing and taking notes on literature relevant to the subject matter. In the Qur'an, Allah has explained human development, namely in Q.S. Ghafir verse 67 and Q.S. Al-Hajj verse 5. Developmental tasks, especially at school age (students) require help/family factors and the educational environment so that students are able to fulfill their developmental tasks. This is explained in the hadith of Rasulullah Saw in HR. Abu Dawud, no.495 and authenticated by Al-Alban in Sahih Abi Dawud. Meanwhile, the factors that influence student development are hereditary factors and student environmental factors. Keywords: Learner Development; Qur'anic and Hadith Perspectives.